PENGARUH RASIO PROFITABILITAS TERHADAP PERTUMBUHAN LABA DENGAN RASIO KINERJA OPERASI DAN RASIO PASAR SEBAGAI MODERATING VARIABEL PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI DASAR DAN KIMIA TAHUN 2016-2018 - Fajar Sari Septiyani; Mishelei Loen, SE., M.Si. (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2020)
This research was conducted at Industrial and Chemical Sector Manufacturing Companies listed on the Indonesia Stock Exchange Period 2016-2018. The purpose of this study is to determine the Profitability Ratio to profit growth with the ratio of operating performance and market ratio as a moderating variable. The collection technique in this study the type of data used is secondary data while the method of analysis uses quantitative analysis. From the results of the research that has been done, it is obtained that the Profitability Ratio shows that there is a positive and significant effect on Profit Growth. The Operating Performance Ratio which moderates the Profitability Ratio to Profit Growth shows there is a negative and significant effect on Profit Growth. While the Market Ratio which moderates the Profitability Ratio to Profit Growth shows there is a negative and not significant effect on Profit Growth.